KNOWLEDGE OF USERS OF A SURGERY CLINIC ABOUT THE OCURRENCE OF INCIDENTS - Ana Lúcia Queiroz Bezerra; Thaynara de Oliveira Silva; Thatianny Tanferri de Brito Paranaguá; Adrielle Cristina Silva Souza; Ana Elisa Bauer de Camargo Silva; Cristiane Chagas Teixeira (Universidade Federal do Paraná, 2016)
The aim of this study was to identify the occurrence of incidents that are noticed by patients during their hospital stay, to assess users views of the occurrence of incidents, and to classify noticed incidents as to type, causes, and consequences. This is a descriptive, cross-sectional study conducted through interviews with 80 patients admitted to the surgery clinic of a teaching hospital in 2014, guided by a validated instrument. Exposure to an incident was noticed by 17.5% of patients. Fourteen types of incidents were noticed, with nine being adverse events, four near-misses, and one an incident with no damage. The most noticeable incidents to the patient were those resulting from the medication administration process. Although within the context of care, many professionals have not yet recognized the importance of involving users to prevent incidents. In addition, educational activities focusing on patient safety for the empowerment of users are required.